Discrimination on the Child Care Market: A Nationwide Field Experiment - Henning Hermes; Philipp Lergetporer; Fabian Mierisch; Frauke Peter; Simon Wiederhold (Institute of Labor Economics (IZA), 2023)
We provide the first causal evidence of discrimination against migrants seeking child care. We send emails from fictitious parents to > 18, 000 early child care centers across Germany, asking if there is a slot available and how to apply. Randomly varying names to signal migration background, we find that migrants receive 4.4 percentage points fewer responses. Responses to migrants also contain substantially fewer slot offers, are shorter, and less encouraging. Exploring channels, discrimination against migrants does not differ by the perceived educational background of the email sender. However, it does differ by regional characteristics, being stronger in areas with lower shares of migrants in child care, higher right-wing vote shares, and lower financial resources. Discrimination on the child care market likely perpetuates existing inequalities of opportunities for disadvantaged children.
Keywords: J13; J18; J22; C93; 330; inequality; child care; discrimination; information provision; field experiment